The Problem of Benzodiazepine Use and Its Extent in the Driver Population: A Population-Based Registry Study - Herrera-Gómez, Francisco; Gutierrez-Abejón, Eduardo; Criado-Espegel, Paloma; Álvarez, F. Javier (Frontiers in Pharmacology, 2018)
Background. Benzodiazepines are driving-impairing medicines (DIM). This study presents current consumption of dispensed benzodiazepines in the Spanish general population, with a focus in pattern of use and concomitant medicines consumed with. Methods. A population-based registry study was carried out to assess the year-2016 granted benzodiazepines dispensation in Castile and León. Weighting was performed to obtain the adjusted benzodiazepine consumption for licensed drivers according to age and gender using our national drivers' license census data. Results. Benzodiazepines were used by 15.38% of the general population and 10.97% of drivers. Nearly 2% of the population and more than 1% of drivers took these medicines every day. The amount consumed (until 3 or more benzodiazepines per day) and concomitant use of other DIM were also higher. Women were the most frequent consumers, and anxiolytic use was usual. Consumption increases with age, but there were differences between men and women drivers from 60 years old. Conclusions. The current use of benzodiazepines must serve to awareness of the healthcare personnel, patients, and authorities on their risks, above all on the road safety.